ChemInform Abstract: Novel Method of Synthesis of Quaternary Ammonium Tribromides and Investigation of Catalytic Role of Benzyltrimethylammonium Tribromide in Oxidation of Alcohols to Carbonyl Compounds. Issue 31 (11th July 2013) - Dey, Madhudeepa; Dhar, Siddhartha Sankar; Kalita, Mukul
Abstract Benzyltrimethylammonium tribromide is used as an efficient catalyst for the oxidation of primary and secondary alcohols to the corresponding carbonyl compounds.